Urinary iodine in second trimester of pregnancy: A cross sectional study in tertiary care hospital of Belagavi - Basnet, Bibek; Patil, Anuradha; Metgud, Shridevi; Singh, Lokjan; Parajuli, Keshab; Basnet, Bikram (Asian Journal of Medical Sciences, 2020)
Background: Iodine is a nutritionally important trace element and its deficiency is a common health problem affecting a huge population, particularly pregnant women and children. The physiological role of iodine in the human body is synthesis of thyroid hormones. Thyroxine is approximately 60% iodine by weight. If iodine intake falls below approximately 100μg/day, Thyroid Stimulating Hormone (TSH) secretion is augmented, which increases plasma inorganic iodide clearance. Aims and Objective: To correlate urinary iodine with serum TSH in the second trimester of pregnant women. Material and Methods: One hundred five subjects were included in the study from tertiary care hospital. A random urine sample was collected. Iodine was estimated by ammonium persulfate method and TSH values were collected from the OBG department of the subjects enrolled. Statistics: Pearson correlation coefficient was done. Results: Median UI 138.50 (29.80-350.51) μg/L, median TSH 1.90(0.17-7.46) mIU/L. There was no significant correlation between UI and serum TSH with r = (0.0873, (p = 0.3756). Conclusion: Urinary iodine is a marker for population iodine status. A preferable biomarker is necessary to know the iodine status of individual which include not only nutritional biomarker and also required to organise reference range for TSH.